Long-Term Ammonia Toxicity in the Hepatopancreas of Swimming Crab Portunus trituberculatus: Cellular Stress Response and Tissue Damage - Lu, Yunliang; Zhang, Jingyan; Cao, Jianwei; Liu, Ping; Li, Jian; Meng, Xianliang (Frontiers in Marine Science, 2022)
Ammonia is the most common contaminant in aquaculture systems. Due to the unexpected deterioration of natural seawater quality caused by harmful alga blooms in summer, the water exchange cycle for the culture ponds of the swimming crab Portunus trituberculatus, an important aquaculture species in China, is often much longer, and the crabs may be exposed to long-term ammonia stress. However, little information is available regarding the long-term effects of ammonia in marine decapod crustaceans. Therefore, it is of great significance to understand the toxic effects of prolonged ammonia in decapods. In this study, alteration of histology, cellular stress responses, and apoptosis in hepatopancreas of P. trituberculatus, an important aquaculture species, during ammonia stress (5, 15 and 45 mg⸱L-1) for 1, 7 and 15 d and recovery at normal condition for 7 d, were analyzed. Our results demonstrated a serious impact of long-term (15 d) ammonia stress by depressing crab cellular stress response (CSR) especially when ammonia concentration exceeds 15 mg⸱L-1. Overall, 1 d and 7 d ammonia stress induced CSR, evidenced by upregulated expression of the genes involved in antioxidant defense, apoptosis , heat shock response (HSR), unfolded protein response (UPR) and DNA damage response (DDR). However, long-term (15 d) ammonia stress, especially when exposed to ammonia of 15 and 45 mg⸱L-1, resulted in higher level of apoptosis and severe damage of hepatopancreas, which may be related to the depressed CSR including antioxidant defense, HSR, UPR and DDR. After recovery, we noticed that expression of many genes involved in apoptosis, antioxidant response, HSR, UPR and DDR in the groups exposed to ammonia at 15 and 45 mg⸱L-1 were still significantly different to that of the control group. In summary, it should be cautious when P. trituberculatus is exposed to ammonia over 15 mg⸱L-1 especially when exposure duration is longer than 15 d, as the CSR could be compromised. The present study provide a reference for comprehensive understanding of CSR in decapod crustaceans under ammonia stress and will be beneficial for management in intensive culture of the swimming crab.